2017
DOI: 10.2503/hortj.okd-052
|View full text |Cite
|
Sign up to set email alerts
|

Chilling Requirements and Blooming Dates of Leading Peach Cultivars and a Promising Early Maturing Peach Selection, Momo Tsukuba 127

Abstract: A major goal of peach breeding programs in Japan is to develop cultivars with lower chilling requirements than the leading cultivars. Low-chill cultivars can be grown in subtropical as well as temperate regions. We investigated the chilling requirements (chill units; CU), heat requirements (growing degree hours; GDH), and blooming dates of 7 leading Japanese peach cultivars, 3 subtropical low-chill cultivars, and a promising new selection, Momo Tsukuba 127. In general, the CU of the 7 leading cultivars were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These results were similar to those reported by Ben Mimoun and DeJong (1999) and Marra et al (2002). The harvest time also depended on cultivars with low chilling (Sawamura et al, 2017) and location (Marra et al, 2002). In previous studies, the harvest data for peach-nectarines were in the range of May 1-7 in Italy (Falqui et al, 1994) and May 5-16 in Turkey (Kuden et al, 2007).…”
Section: Phenological Observationssupporting
confidence: 87%
See 1 more Smart Citation
“…These results were similar to those reported by Ben Mimoun and DeJong (1999) and Marra et al (2002). The harvest time also depended on cultivars with low chilling (Sawamura et al, 2017) and location (Marra et al, 2002). In previous studies, the harvest data for peach-nectarines were in the range of May 1-7 in Italy (Falqui et al, 1994) and May 5-16 in Turkey (Kuden et al, 2007).…”
Section: Phenological Observationssupporting
confidence: 87%
“…Heat requirements were calculated as the accumulation of growing degree hours (GDH) based on hourly air temperatures above 4.5 °C (Sawamura et al, 2017). Trees have no additional growth advantage at temperatures above 25 °C; therefore, the temperatures above 25 °C were accepted as equal to 25 °C.…”
Section: Heat Requirementsmentioning
confidence: 99%
“…Significant differences between observed and expected bloom dates were documented for the low-chill cultivars ‘Patty’ and ‘Carla’, while the smallest differences were determined for ‘Sweet Dream’, ‘Big Top’ and ‘Catherina’. In a recent study by Sawamura et al [ 31 ], observed bloom dates collected for three peach cultivars and one selection grown in different locations in Japan were compared with predicted bloom dates calculated with the Utah Model. In agreement with our results, the authors found low suitability of this model for the low-chill selection.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, chilling accumulation was substantially reduced at low latitudes, causing daylength to play a more important role by interacting with temperature. The chilling threshold to break dormancy might vary across space as well, and trees from high latitudes might exhibit higher chilling requirements ( Sawamura et al, 2017 ). Since warming rates increase with latitude ( IPCC, 2021 ), chilling accumulation might also become insufficient at high latitudes in the future, and thus, daylength may affect future budburst dates at both high- and low-latitude regions.…”
Section: Discussionmentioning
confidence: 99%